PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XII MAN SIGI PADA SOAL MATRIKS DI TINJAU DARI GAYA BELAJAR VISUAL: Profile of Studens’ Mathematical Communication Ability in Class XII MAN SIGI on Matrix Questions Reviewed From Visual Learning Style - Sarita, Rahma; Karniman, Tegoeh S.; Alfisyahra, Alfisyahra; Anggraini, Anggraini (Universitas Tadulako, 2024)
The aim of this research is to obtain a description of the mathematical communication ability profile of MAN SIGI students in solving sathematical problems in view of visual learning style. This type of research is descriptive with a qualitative approach. The subjects of this research were students of class XII IPA 1 MAN SIGI who had a visual learning style. Characteristics of the visual learning style are the ability to remember information seen and prefer reading to listening to other people's explanations. Determining the subject in this research, prospective researchers gave a learning style questionnaire consisting of 10 questions, and each question had 3 choices: a, b, c. If a student most dominantly chose a, then the student had a visual learning style; if a student most dominantly chose b, then the student has an auditory learning style; if a student chooses a lot of c's, then the student has a kinesthetic learning style. Based on the results of the questionnaire, 1 student was selected with a visual learning style. If there were several students who had a visual learning style, the researcher discussed with the study teacher about students who had good communication skills and students who received information easily. Data was collected through written tests and interviews. The results of this research showed that the subjects with a visual learning style are able to write down and explain well all the information obtained from the questions.